2020
DOI: 10.1021/acs.est.0c04192
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Facilitating Candidatus Nitrotoga To Be Prevalent Nitrite-Oxidizing Bacteria in Activated Sludge

Abstract: Nitrite oxidation is the primary pathway that generates nitrate in engineered systems. However, little is known about the role of a novel nitrite-oxidizing bacteria (NOB) genus Candidatus Nitrotoga in activated sludge systems. To elucidate key factors that impact NOB community composition, laboratory-scale sequencing batch reactors (SBRs) were designed and operated under the same conditions as real wastewater treatment plants to achieve considerable nitrogen removal and similar community; then, different condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 52 publications
2
37
1
Order By: Relevance
“…This might hint at a lifestyle adapted to low oxygen concentrations, which is in accordance with employing a high‐affinity cbb 3 oxidase. Similar to their nitrite affinities, however, the oxygen affinities of Nitrotoga also seem lower than those of Nitrospira (Nowka et al ., 2015a; Zheng et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This might hint at a lifestyle adapted to low oxygen concentrations, which is in accordance with employing a high‐affinity cbb 3 oxidase. Similar to their nitrite affinities, however, the oxygen affinities of Nitrotoga also seem lower than those of Nitrospira (Nowka et al ., 2015a; Zheng et al ., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This recently described Ca . Nitrotoga species can be functionally and sometimes dominant important nitrite oxidizers in WWTPs due to their relatively higher resistance to free nitrous acid and free ammonia than other NOB and the presence of complete pathways for hydrogen and sulfite oxidation, suggesting that alternative energy metabolisms enable these bacteria to survive nitrite depletion 40 42 .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, close relatives of mesophilic Cand . Nitrotoga fabula were less competitive with Nitrospira at cold conditions and seem to be responsible for nitrite oxidation in warm water (> 20 °C) N-removal systems as observed in China and Australia (Liu et al 2021 ; Zheng et al 2020 ; Petrovski et al 2020 ; Table S1 ).…”
Section: Competition Of Cand Nitrotoga With Nitrospira and Nitrobactermentioning
confidence: 95%
“…However, in an SBR, Cand. Nitrotoga was found to have a lower affinity to dissolved oxygen than Nitrospira (Zheng et al 2020 ; Table 1 and S1 ), and a stepwise increase of the DO level in a PNA reactor from 0.4 to 1.8 mg L −1 (13–56 µM) led to an increase of Cand. Nitrotoga versus Nitrospira (Qian et al 2021 ), which confirmed the tolerance of Cand.…”
Section: Competition Of Cand Nitrotoga With Nitrospira and Nitrobactermentioning
confidence: 99%
See 1 more Smart Citation